(untitled) (Asian Journal of Medical and Biological Research, 2021)
The COVID-19 pandemic has cost a large number of lives worldwide. Most of the COVID-19 patients recover within two weeks of illness, but many survivors are experiencing different post COVID-19 clinical complications. In this cross-sectional retrospective study, we investigated the immediate and post COVID-19 complications with secondary effects in symptomatic and asymptomatic COVID-19 patients of Bangladesh. A total of 632 patients diagnosed with COVID-19 from December, 2020 to February, 2021 were included in this study. The data were collected by telephone interview with patients consent and reviewing their call records using questionnaire and checklist. Results demonstrate that among the 632 patients, 77.53 % of cases were symptomatic, where fever was the most common symptom (82.24%). The other symptoms were headache (58.16%), sore throat (53.65%), cough (45.51%), weakness (41.22%), breathlessness (40%), loss of smell (37.55%), tastelessness (31.84%), diarrhea (19.39%), and vomiting (14.69%). Comorbidities like asthma, hypertension, diabetes mellitus (DM), cardiovascular disease, and other chronic diseases were pronounced in symptomatic patients. Post COVID-19 complications varied significantly (P<0.05) between the symptomatic and asymptomatic observations. Asthma, hypertension, and diabetes were newly reported in symptomatic patients with the rate of 3.06 %, 2.45 %, and 2.24 %, respectively, while the proportions were 1.41%, 1.41%, and 0.70% for the asymptomatic group. Tiredness, weight loss, hair loss, and insomnia were the most observed post COVID-19 complications found higher in symptomatic patients than in asymptomatic groups. A newly developed visual anomaly was also identified in the symptomatic group (1.42%), which was absent in asymptomatic COVID-19 recovered patients. These findings concluded that post-COVID-19 complications were high in symptomatic and comorbid patients compared with asymptomatic individuals. We hope that this study will contribute in post COVID-19 management and help the concerned authority toward decision making in the treatment of post-COVID-19 complications. Asian J. Med. Biol. Res. 2021, 7 (2), 191-201